High-temperature kinetic magnetism in triangular lattices - Ivan Morera; Márton Kanász-Nagy; Tomasz Smolenski; Livio Ciorciaro; Ataç Imamoğlu; Eugene Demler (Physical Review Research, 2023)
We study kinetic magnetism for the Fermi-Hubbard model in triangular lattices. We focus on the regime of strong interactions, U≫t, and filling factors around one electron per site. For temperatures well above the hopping strength t, the Curie-Weiss form of the magnetic susceptibility suggests two complementary forms of kinetic magnetism. In the case of hole doping, antiferromagnetic polarons originate from kinetic frustration of individual holes, whereas for electron doping, Nagaoka-type ferromagnetic correlations are induced by propagating doublons. These results provide a possible theoretical explanation of recent experimental results in moiré transition metaldichalcogenide materials and cold atom systems. To understand many-body states arising from antiferromagentic polarons at low temperatures, we study hole-doped systems in finite magnetic fields. At low dopings and intermediate magnetic fields, we find a magnetic polaron phase, separated from the fully polarized state by a metamagnetic transition. With decreasing magnetic field, the system shows a tendency to phase separate with hole-rich regions forming antiferromagnetic spin bags. We demonstrate that direct observations of magnetic polarons in triangular lattices can be achieved in experiments with ultracold atoms, which allow measurements of three point hole-spin-spin correlations.